2012
DOI: 10.1007/s10354-011-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Kosten des chronischen unspezifischen Kreuzschmerzes in Österreich – eine Untersuchung an Patienten in aktueller Behandlung

Abstract: The objective of this pilot study was to evaluate the annual direct costs of chronic non-specific low back pain in Austria in patients currently undergoing in-patient rehabilitation or out-patient treatment. 48 patients participated in the study. Average direct medical costs per patient year as paid by the sick funds were € 1443,-, in-patient rehabilitation was the single most expensive direct cost factor. Non-medical costs, that is, mainly household assistance and home adaptations, were € 394,-; deductibles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(19 reference statements)
0
4
1
Order By: Relevance
“…In comparison with another Austrian study measuring the direct costs of chronic low back pain in 2008 (EUR 1837 in 2008) [11], total direct medical costs were considerably higher in this study. Despite methodological discrepancies between the two analyses, inpatient rehabilitation and out-of-pocket costs were also found to be the most expensive cost factor in this earlier study [11], which is consistent with our findings. Compared to our study, total costs from the societal perspective were found to be lower in a Portuguese study (EUR 1883 in 2010) and in a Swedish study (EUR 6429 in 2008) [12, 14].…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In comparison with another Austrian study measuring the direct costs of chronic low back pain in 2008 (EUR 1837 in 2008) [11], total direct medical costs were considerably higher in this study. Despite methodological discrepancies between the two analyses, inpatient rehabilitation and out-of-pocket costs were also found to be the most expensive cost factor in this earlier study [11], which is consistent with our findings. Compared to our study, total costs from the societal perspective were found to be lower in a Portuguese study (EUR 1883 in 2010) and in a Swedish study (EUR 6429 in 2008) [12, 14].…”
Section: Discussioncontrasting
confidence: 81%
“…To assess the societal and economic impact of chronic pain, several cost-of-illness studies have been conducted across Europe (e.g. [1117]). Differences in methodologies, costing approaches and populations, however, make comparisons across studies difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diseases of the respiratory system (J00–J99) Bronchial AsthmaBULIvanova et al [20] a 2014112Hospital costRetrospective chart review200–393 c 200–393 c NRNR2.8-5.5% COPDBULROUKyuchukov et al [21] a Stâmbu et al [37]NR20068485Hospital and patientNRProspective cohortInterview data183921038982103NRNRNRNR25.9%21.9% Lower respiratory tract infectionBULGlogovska et al [19] a NR1441 ambulatory + 353 hospitalizedHealth systemNRNR1218NRNR17.2% PneumoniaCZEHUNPOLSVKTichopad et al [76]2010258NR198315NRClaims dataAges 50–64/> 651194/7861009/686714/4721685/1111Ages 50–64/age > 65708/786686/686472/4721190/1111Ages:50-64/> 65486/0323/0242/0495/06.6%/4.3%8.0%/5.4%5.9%/3.9%10.8%/7.1% Streptococcus pneumoniae ROUStoicescu et al [93]200448,200Public payerClaims data8.3 million8.3 millionNRNRNAXIII. Diseases of the musculoskeletal system and connective tissue (M00.0–M99.9) Chronic non-specific back painAUTWagner et al [64] a 200848…”
Section: Methodsmentioning
confidence: 99%
“…These issues as well as the growing prevalence put LBP as a major public health problem, associated with increasing costs for social systems. Results of a recent Austrian study looking into societal costs linked to chronic pain issues reported overall annual costs of 10,191 Euros per patient, with inpatient rehabilitation, and out-of-pocket costs being identified as the two most expensive costs factors, the latter being also the conclusion of a 2008 Austrian study [11, 12].…”
Section: Introductionmentioning
confidence: 99%